Molecular Characterization and Clinical Outcomes of Klebsiella pneumoniae in Neonatal Sepsis: A Three-Year Molecular Epidemiological Study - Oscar Villavicencio-Carrisoza; Orly Grobeisen-Duque; Janet Flores-Villanueva; Jimena Lopez-Dueñas; María Guadalupe Martínez-Salazar; Moises Leon-Juarez; Maria Isabel Villegas-Mota; Juan Xicohtencatl-Cortes; Sara A. Ochoa; Irma Eloisa Monroy-Muñoz; Ricardo Figueroa-Damian; Graciela Villeda-Gabriel; et al. (Children, 2026)
Background: Klebsiella pneumoniae is one of the leading causes of healthcare-associated neonatal sepsis, with increasing antibiotic resistance and virulence representing major challenges for neonatal care. This study aimed to characterize the molecular epidemiology of K. pneumoniae isolates causing neonatal sepsis at a tertiary referral center in Mexico City and to evaluate the relationship between antibacterial resistance, virulence determinants, clonal dissemination, and neonatal outcomes. Methods: A retrospective observational study was conducted including 57 K. pneumoniae isolates recovered from 39 neonates with culture-confirmed sepsis between 2021 and 2023. Antibiotic susceptibility testing, ESBL production, multidrug resistance, detection of resistance- and virulence-associated genes, multilocus sequence typing, and clinical outcome analyses were performed. Results: A progressive increase in antibiotic resistance and virulence was observed throughout the study period. MDR and ESBL-producing isolates increased from 44.4% and 33.3% in 2021 to 78.9% each in 2023, while isolates with high virulence gene burden increased from 33.3% to 73.7%. The most prevalent resistance genes were blaCTX-M, aac(6′)-Ib, and aac(3)-IIa, whereas uge, ycfM, fimD, and entB were the predominant virulence determinants. High-virulence gene burden was associated with increased prevalence of blaCTX-M and aac(6′)-Ib, while ESBL-producing isolates were associated with ybtS, and MDR isolates were associated with ybtS and uge. PFGE identified a predominant clone (Cluster B) with 100% similarity, characterized by ST45 isolates and significantly higher resistance and virulence profiles. High-virulence isolates were associated with thrombocytopenia and extreme prematurity. Conclusions: K. pneumoniae isolates causing sepsis are increasing antibiotic resistance, virulence gene burden, and clonal dissemination over the three-year study period. The convergence of resistance and virulence determinants highlights the emergence of high-risk hospital-adapted clones and underscores the importance of continuous molecular surveillance to improve infection control and optimize neonatal management.